Effect of double adhesive layer application on micro-tensile dentin bond strength of a universal adhesive - Afnan O. Al-Zain; Afnan O. Al-Zain; Asrar Albuqayli; Abdulaziz Albogami; Abdulghani Alkudsi; Meshari Alwabiri; Abdullah T. Koshak; Hattan Alsefri; Eliseu A. Munchow (Frontiers Media S.A., 2024)
IntroductionAchieving optimal dentin bond strength is crucial for the long-term success of adhesive restorations. This study aims to evaluate the impact of double adhesive layer application, with and without light curing between applications, on the micro-tensile dentin bond strength (µ-TBS) of a universal adhesive, in comparison to the conventional single-layer application.MethodsIntact human molars were divided into three groups (n = 15) according to the adhesive application technique using a universal self-etch adhesive (Tetric N-Bond Universal, Ivoclar) as follows: (1) according to the manufacturer's instructions, (2) double-layer application without light curing between layers, and (3) double-layer application with light curing between layers. Samples were immediately tested for µ-TBS, with failure types recorded as adhesive, cohesive, or mixed. Representative samples were observed by scanning electron microscopy. Data were analyzed using multiple-way ANOVA (α = 0.05).ResultsThe double adhesive layer with and without light curing between layers showed similar μ-TBS to that of the control group (p > 0.05).DiscussionFrom a clinical perspective, these findings suggest that the accurate application of a single layer of a universal adhesive can be as effective as more complex techniques. Additionally, the use of universal bonding agents may have contributed to the outcomes observed in this study. In conclusion, double adhesive layer application and light curing between adhesive layers did not increase the µ-TBS with the universal adhesive agent explored.